The Influence of Loading and Unloading Service Quality, Human Resource Availability, Operational Efficiency, and Information Technology on Customer Satisfaction At PT Pelindo Terminal TPK Pantoloan Container Palu Central Sulawesi - Idrus Usu; Debby R Karundeng; Muhammad Lutfillah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aims to analyze the influence of loading and unloading service quality, availability of human resources, operational efficiency, and information technology on customer satisfaction simultaneously at PT Pelindo Terminal Petikemas (TPK) Pantoloan, Palu, Central Sulawesi. The research method uses a quantitative approach with multiple linear regression analysis techniques. The research sample consisted of customers who used TPK Pantoloan port services. The results showed that the four variables simultaneously had a significant effect on customer satisfaction with an F test value of 103.022 and a significance level of 0.000. The determination coefficient (R²) of 0.848 indicates that 84.8% of the variation in customer satisfaction can be explained by the variables of loading and unloading service quality, availability of human resources, operational efficiency, and information technology. These findings confirm the importance of integration between service factors, human resources, efficiency, and technology in improving customer satisfaction at container ports. The managerial implications of this study are the need for continuous improvement in service quality, human resource competency development, optimization of operational efficiency, and more intensive use of information technology. This research makes an empirical contribution to port management, especially in the Central Sulawesi region which has unique operational characteristics.